What do we Know about Complex-Contrast Training? A Systematic Scoping Review - Rohit K. Thapa; Anthony Weldon; Tomás T. Freitas; Daniel Boullosa; José Afonso; Urs Granacher; Rodrigo Ramirez-Campillo (SpringerOpen, 2024)
Abstract Background The complex-contrast training (CCT) method utilizes two exercises with different loads and movement velocities in a set-by-set fashion to induce multiple neuromuscular adaptations. The speculated primary mechanism involves the post-activation potentiation or post-activation performance enhancement (PAPE) of the muscles used during the heavy load (low velocity) exercise, thereby improving the performance of lower load (high velocity) exercise. However, no previous study has attempted to systematically synthesize the available evidence on CCT (e.g., if post-activation potentiation or PAPE was measured during the training sessions during the intervention period). This study aimed to synthesize the available evidence on CCT using a systematic scoping review approach. More specifically, we identified gaps in the literature using an evidence gap map (EGM), and provided future directions for research. Methods Three electronic databases (PubMed, Scopus, and Web of Science) were searched up to 20th February 2024. Data were extracted under a PICO framework: (a) Participants-related data (e.g., age, sex, type of sport); (b) Intervention-related data (e.g., duration of training); (c) Comparators (when available); and (d) Outcomes (e.g., measures of physical fitness). Interactive EGMs were created using the EPPI mapper software. Results From the 5,695 records screened, 68 studies were eligible for inclusion, involving 1,821 participants (only 145 females from 5 studies). All CCT interventions lasted ≤ 16 weeks. More than half of the studies assessed countermovement jump, sprint, and maximal strength performances. No studies were identified which examined upper-body CCT exercises alone, and no study assessed PAPE during the CCT sessions. Overall, the available evidence was rated with a low level of confidence. Conclusions In conclusion, whether CCT produces a PAPE that translates into longitudinal performance gains remains unclear. Moreover, the available evidence on the effects of CCT on various outcomes provides low confidence regarding the most effective way to implement this training method, particularly among females, and beyond long-term interventions.